2020
DOI: 10.1152/ajpheart.00613.2019
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month systems toxicology inhalation study in ApoE−/− mice demonstrates reduced cardiovascular effects of E-vapor aerosols compared with cigarette smoke

Abstract: Analysis of key urinary oxidative stress markers and proinflammatory cytokines showed an absence of oxidative stress and inflammation in the animals exposed to E-vapor aerosols. Conversely, animals exposed to conventional cigarette smoke had high urinary levels of these markers. When compared with conventional cigarette smoke, E-vapor aerosols induced smaller atherosclerotic plaque surface area and volume. Systolic and diastolic cardiac function, as well as endothelial function, were further significantly less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 167 publications
3
43
0
Order By: Relevance
“…Another recent study by Szostak et al also found that e-cigarette aerosols were less harmful to the CV system than the smoke from cigarettes [73]. This study included five groups of ApoE −/− mice-control, test cigarette, carrier aerosol, nicotine-containing base aerosol, and test vape aerosol with nicotine and flavoring.…”
Section: Nicotine Vaporsmentioning
confidence: 95%
See 3 more Smart Citations
“…Another recent study by Szostak et al also found that e-cigarette aerosols were less harmful to the CV system than the smoke from cigarettes [73]. This study included five groups of ApoE −/− mice-control, test cigarette, carrier aerosol, nicotine-containing base aerosol, and test vape aerosol with nicotine and flavoring.…”
Section: Nicotine Vaporsmentioning
confidence: 95%
“…Murine models are most commonly used for nicotine and tobacco studies [70][71][72][73][74], although other animal models, including primates and C. elegans, have been used for behavioral and metabolic studies [75][76][77]. Species differences exist in nicotine metabolism, and non-human primates metabolize nicotine in a similar manner to humans [78].…”
Section: Tobacco and Nicotine In Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The APS portfolio of publications includes our sister journal, the American Journal of Physiology-Heart and Circulatory Physiology, which also contributes publications on the physiology of lung-heart interactions. These contributions include stateof-the-art Reviews, such as a recent treatise on cardiovascular adaptations to particle inhalation exposure (23); as well as Research Articles, which largely deal with the cardiac consequences of pulmonary hypertension (42), or the impact of heated tobacco products and vaping on the cardiovascular system (40). Thus, together with the American Journal of Physiology-Heart and Circulatory Physiology under the stewardship of Editor-in-Chief Dr. Irving H. Zucker, our Journal is one of two journals within the APS publications portfolio that regularly contributes reports to the expanding body of literature on the cardiac causes and consequences of lung disease.…”
Section: World Heart Daymentioning
confidence: 99%